Anterolateral intervertebral disc herniation presenting as visceral pain in a patient with renal keratinising desquamative squamous metaplasia. Issue 4 (23rd April 2021) - Bennett, Andrew S; Gray, Caitlin Mcauliffe; Ruchi, Rupam; Kumar, Sanjeev
Abstract : We report the case of a 70-year-old man who presented to the clinic with back pain and presumed chronic kidney pain from renal keratinising desquamative squamous metaplasia, in which he would intermittently pass keratin plugs in urine. The pain had a visceral-sounding component that was inconsistent with renal colic. MRI of the spine revealed anterolateral disc bulges, which were likely irritating the anterolateral sympathetic nerves of the intervertebral disc, mimicking visceral pain. Transforaminal epidural steroid injection (TFESI) was performed at the levels of the disc bulges. He had no pain during passage of keratin plugs for 6.5 months after the TFESI which could be attributed to the expected duration of symptoms relief after a properly done TFESI.